Split-Framework in Mandibular Implant-Supported Prosthesis - Danny Omar Mendoza Marin; Kássia de Carvalho Dias; André Gustavo Paleari; Ana Carolina Pero; João Neudenir Arioli Filho; Marco Antonio Compagnoni (Case Reports in Dentistry)
During oral rehabilitation of an edentulous patient with an implant-supported prosthesis, mandibular flexure must be considered an important biomechanical factor when planning the metal framework design, especially if implants are installed posterior to the interforaminal region. When an edentulous mandible is restored with a fixed implant-supported prosthesis connected by a fixed full-arch framework, mandibular flexure may cause needless stress in the overall restorative system and lead to screw loosening, poor fit of prosthesis, loss of the posterior implant, and patient’s discomfort due to deformation properties of the mandible during functional movements. The use of a split-framework could decrease the stress with a precise and passive fit on the implants and restore a more natural functional condition of the mandible, helping in the longevity of the prosthesis. Therefore, the present clinical report describes the oral rehabilitation of an edentulous patient by a mandibular fixed implant-supported prosthesis with a split-framework to compensate for mandibular flexure. Clinical Significance. The present clinical report shows that the use of a split-framework reduced the risk of loss of the posterior implants or screws loosening with acceptable patient comfort over the period of a year. The split-framework might have compensated for the mandibular flexure during functional activities.